2008
DOI: 10.1210/en.2008-0285
|View full text |Cite
|
Sign up to set email alerts
|

Bezafibrate, a Peroxisome Proliferator-Activated Receptors Agonist, Decreases Body Temperature and Enhances Electroencephalogram Delta-Oscillation during Sleep in Mice

Abstract: Peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors belonging to the nuclear receptor family. PPARs play a critical role in lipid and glucose metabolism. We examined whether chronic treatment with bezafibrate, a PPAR agonist, would alter sleep and body temperature (BT). Mice fed with a control diet were monitored for BT, electroencephalogram (EEG), and electromyogram for 48 h under light-dark conditions. After obtaining the baseline recording, the mice were provided w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 39 publications
3
50
0
Order By: Relevance
“…PPAR␣ has also been implicated in a variety of metabolic processes including lipid metabolism and energy homeostasis (1,2), affecting many of the pathways in response to fasting, such as gluconeogenesis, ketogenesis, and fatty acid metabolism. Recent studies showed that FGF21, the endocrine hormone synthesized from a liver PPAR␣ target gene (36), is able to enter into the brain through the blood-brain barrier and up-regulate hypothalamic NPY (37,38). In the present study, fasting and PPAR␣ agonist administration both induced liver FGF21, which confirms previous observations (2,39).…”
Section: Discussionsupporting
confidence: 91%
“…PPAR␣ has also been implicated in a variety of metabolic processes including lipid metabolism and energy homeostasis (1,2), affecting many of the pathways in response to fasting, such as gluconeogenesis, ketogenesis, and fatty acid metabolism. Recent studies showed that FGF21, the endocrine hormone synthesized from a liver PPAR␣ target gene (36), is able to enter into the brain through the blood-brain barrier and up-regulate hypothalamic NPY (37,38). In the present study, fasting and PPAR␣ agonist administration both induced liver FGF21, which confirms previous observations (2,39).…”
Section: Discussionsupporting
confidence: 91%
“…The plausible mechanism by which fat oxidation increases NREM sleep is an increase in plasma concentration of ketone bodies. Another study in mice reported that increases of the plasma ketone ratio (acetoacetate/b-hydroxybutyrate) were associated with increased EEG delta power in NREM sleep (26), which has been used as physiological markers of deep sleep and homeostatic need for sleep (27). Plasma ketone bodies were not measured in the present study, but it is reasonable to expect their increase after HFD consumption (28).…”
Section: Discussionmentioning
confidence: 99%
“…FGF21 administration increases NPY mRNA levels in the hypothalamus (Coskun et al 2008). Similarly, treatment of mice with a fibrate PPAR agonist induces hypothermia, accompanied by increased NPY expression in the hypothalamus, and an NPY-Y1 receptor antagonist prevents this fibrate-mediated hypothermia (Chikahisa et al 2008). However, neither PPARa nor FGF21 is essential for fasting-mediated induction of NPY (Oishi et al 2010).…”
Section: Physiological Actions Of Fgf21mentioning
confidence: 99%